2016
DOI: 10.1111/hiv.12473
|View full text |Cite
|
Sign up to set email alerts
|

Rate, correlates and outcomes of repeat pregnancy in HIV‐infected women

Abstract: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
2
9
1
Order By: Relevance
“…Trends and patterns of pregnancy and childbirth may vary between different countries. Our results are consistent with other studies showing that women with HIV infection are increasingly choosing to become pregnant, even to have repeated pregnancies after their HIV diagnosis [51719].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Trends and patterns of pregnancy and childbirth may vary between different countries. Our results are consistent with other studies showing that women with HIV infection are increasingly choosing to become pregnant, even to have repeated pregnancies after their HIV diagnosis [51719].…”
Section: Discussionsupporting
confidence: 93%
“…One woman conceived 4 times after HIV diagnosis including 3 live births and 1 miscarriage. Previous studies have reported a recent increase in repeated pregnancies among women with HIV infection [5171819]. Repeated pregnancies are not just a consequence of lack of or ineffective contraception, but also reflect the desire of these individuals to have multiple children [517].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These long-term complications have not been studied in HIV-related pregnancies. However, an increasing proportion of women living with HIV desire to have several children [ 28 , 29 ]. This was also true in our study, where 37% of women had more than one child after being diagnosed with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…4 Likewise, Floridia et al showed that the CD4 count early in pregnancy and viral suppression at delivery improved in repeat pregnancies, and was associated with greater ART coverage. 5 However, specific differences in antiretroviral (ARV) regimens in repeat pregnancies and associations with birth outcomes were not examined.…”
Section: Introductionmentioning
confidence: 99%